Pengaruh Customer Experience dan E-Service Quality Terhadap Kepuasan Pelanggan pada Pengguna Aplikasi PLN Mobile - Ramadhan, Andhika Reyhant; Murtiyanto, Rizky Kurniawan; Evelina, Tri Yulistyawati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Advances in information technology have driven PT PLN (Persero) to undertake a digital transformation through the PLN Mobile app, a fast, easy, and efficient platform for electricity services. However, there are still customer complaints regarding delays in power outage information, unresponsive notifications, and the length of time it takes to resolve complaints, all of which can affect customer satisfaction. This study aims to analyze the influence of Customer Experience and E-Service Quality on customer satisfaction among users of the PLN Mobile App at PT PLN (Persero) ULP Kota Batu. This study employs a quantitative approach using a survey method. Data were collected via a Google Forms questionnaire from 100 respondents who are customers of PT PLN (Persero) ULP Kota Batu and have used the PLN Mobile App, using purposive sampling. Data analysis was performed using IBM SPSS Statistics 25 through descriptive analysis, validity and reliability tests, classical assumptions, multiple linear regression, the coefficient of determination, t-tests, and F-tests. The results of the study indicate that Customer Experience has a positive and significant effect on customer satisfaction (t-value = 4.901; sig. = 0.000), as does E-Service Quality (t-value = 3.199; sig. = 0.002). Simultaneously, both variables have a positive and significant effect on customer satisfaction (F-calculated = 57.290; sig. = 0.000) with an R-squared of 0.542. Thus, Customer Experience and E-Service Quality play a crucial role in enhancing customer satisfaction among users of the PLN Mobile app.